Effect of spraying l‐menthol on peristalsis resumption during endoscopic submucosal dissection of gastric tumors. Issue 6 (6th May 2021) - Ishiyama, Akiyoshi; Namikawa, Ken; Tokai, Yoshitaka; Yoshimizu, Shoichi; Horiuchi, Yusuke; Yoshio, Toshiyuki; Hirasawa, Toshiaki; Tsuchida, Tomohiro; Itoh, Fumio; Fujisaki, Junko
Abstract: Background and Aim: l ‐Menthol has smooth muscle‐relaxing and antiperistaltic effects. We examined its effectiveness against peristalsis resumption during endoscopic submucosal dissection (ESD) of gastric tumors. Methods: We retrospectively examined clinical data of 485 patients (501 lesions) who underwent ESD for upper gastrointestinal tumors in 2017. We included 119 patients (127 lesions) in whom peristaltic movement resumed during ESD and l ‐menthol was applied; 366 patients (374 lesions) without l ‐menthol application were used as controls. Video recordings were reviewed to determine whether l ‐menthol suppressed peristalsis resumption. Results: In cases with l ‐menthol application, 2 (2.9%), 36 (14.3%), and 89 (71.2%) lesions were found in the upper (U), middle (M), and lower (L) regions, respectively. In the control group, the corresponding values were 66 (17.6%), 215 (57.5%), and 93 (24.9%), respectively. l ‐Menthol efficacy was observed in 116 of the 127 treated lesions (91.3%), over 90% of which were in the posterior wall of the U region, anterior wall and greater curvature of the M region, and anterior wall and lesser curvature of the L region. The most and least effective areas for l ‐menthol application were the anterior wall of gastric antrum and posterior wall of the M region, respectively. The mean time from application to peristalsis inhibition was 8.7 s. No adverse effects were observed; perforation and secondary hemorrhage were not significantly different between the groups. Conclusion: Direct l ‐menthol application to the submucosal layer during mucosal resection affects smooth muscles and rapidly inhibits peristalsis resumption. Clinically, l ‐Menthol can be used to suppress peristalsis recurrence during ESD, without adverse effects. Abstract : Direct l ‐menthol application to the submucosal layer during mucosal resection. When peristaltic resumption was seen, we sprayed l ‐menthol on submucosal layer directly. Peristalsis stopped rapidly (8.7 seconds). l ‐menthol was effective in 91.5% cases.